WILL FISH DISAPPEAR BY 2048? - Wanwan Kurniawan (OSEANA, 2020)
In 2006, a tumult arose in the world of fisheries. A controversial paper titled “Impacts of biodiversity loss on ocean ecosystem services” by Worm et al. (2006) was published in Science. The paper was sensational since it alluded to a prediction that global populations of marine fish (finfish and invertebrates) will be 100% collapsed by 2048. The paper was written by a group of marine ecologists and economists in which Boris Worm from Dalhousie University Canada led the authorship. After the paper was published, the issue of fish disappearance in 2048 became hot topics in the world’s mass media. In fact, the Worm et al. paper triggered the debates among researchers. Over time the debates heated up. Surprisingly, a reconciliation took place in 2009, marked by a collaboration between Worm’s team and his critics, writing another paper in Science. The present essay reaffirms the invalidity of the global collapse prediction in 2048 as revealed by many researchers. It is also shown that the Worm et al. paper did not state that all fish will disappear and through the joint paper in 2009, Worm and colleagues have indirectly rectified the prediction already.